STFTiS: Introducing a spatio‐temporal FTiS model to investigate the level of citizens' satisfaction of 311 non‐emergency services. Issue 2 (4th January 2022) - Mohammadi, Reza; Taleai, Mohammad; Alizadeh, Somayeh; Abbasi, Omid Reza
Abstract: Using the 311 service, citizens can help the government gain a deeper understanding of citizens' needs by reporting the status of municipal services. This study proposes the STFTiS model to examine the level of citizens' satisfaction by investigating the spatio‐temporal patterns of 311 reports provided by citizens regarding municipal services. The main novelty of the proposed STFTiS model is its ability to integrate the spatial domain into the traditional FTiS (frequency, time interval, and satisfaction) model. For this purpose, Moran's I index was used to cluster the 311 reports from a spatial perspective. Afterward, the reports were clustered based on the spatial labels and the parameters of time interval and frequency . A fuzzy time series and an autoregressive moving average prediction model have been combined to find the best temporal window for association rule mining. The proposed model was applied to a database of the Boston 311 service. The results from interpreting clusters indicate that Boston's citizens are most interested in government responses to address Transportation and Inspection Service issues. Besides, the most important rule states a strong relationship between the Mayor's 24‐Hour Hotline and Inspection Service reports, with 86% support and 95.7% confidence. The evaluation shows that the STFTiS model has significantly improved the results of the non‐spatial FTiS model. The results can be used by policymakers to effectively manage citizens' needs and provide necessary on‐demand support by discovering the most critical needs of citizens.